Biochar Production from Waste Biomass using Modular Pyrolyzer for Soil Amendment (Chemical Engineering Research Bulletin, 2021)
Nowadays, researchers have found many applications of biochar due to its large surface area, ion and water holding capacity, sheltering possibility for microbes beneficial for the plants’ nutrition intake, carbon sequestration etc. Among several waste biomass feedstock, agricultural waste is a suitable source of biomass for the biochar production. So, in this study, a low cost, modular technology was proposed that can be used at the consumer end to produce biochar of satisfactory quality. In this technology, no separate inert gas feed was required, thereby lowering the cost and complexity of the system. The reactor was designed in a way that most of the oxygen got consumed at the beginning of the process and the residual nitrogen from air maintained a pseudo-inert environment. As potential feedstock for biochar, rice husk and wood chips were considered in this study. Also, to evaluate the quality of produced biochar, proximate analysis and calorific value were measured. The char yields were found to be between 20 to 40%. For rice husk (powdered and granular) and wood chips, the volatile content (%) were 15.88, 19.69 and 25.47 respectively meaning most of the volatiles were released during devolatilization. It was found that biochar can be produced from agricultural waste using this method by farmers in the field without any additional equipment, and the pyrolyzer is modular and portable. Finally, the biochar could be used for soil replenishment. Further work is ongoing on the char characterization to realize the full potential of biochar production from waste biomass.Chemical Engineering Research Bulletin 21(2020) 14-19